/
/
/
Use synthetic division to find the quotient.
Not my Question
Flag Content

# Question : Use synthetic division to find the quotient. : 2151859

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Use synthetic division to find the quotient.

1) (x3 - x2 + 5/x + 2)

A) x2 + 3x + 6 + (-7/x + 2)

B) x2 - 2x + 6 + (6/x + 2)

C) x2 - 3x + 6 + (6/x + 2)

D) x2 - 3x + 6 + (-7/x + 2)

2) (-5x3 - 7x2 + 2x - 8 /x + 2)

A) - (5/2)x2 + - (7/2)x + 1

B) -5x2 + 3x - 4

C) -5x + 3

D) 5x2 - 2x - 4

3) (x4 - 2x3 - 13x2 - 8x - 10/x - 5)

A) x3 + 3x2 + 2x + 2

B) x3 + 3x2 + 4x

C) x3 + 3x2 + 4x + 4

D) x3 + 4x2 + 2x - 2

4) (x5 - 3x4 - 13x3 + 18x2 - 13x - 7/x - 5)

A) x3 + 2x2 - 3x + 3 + (3/x - 5)

B) x4 + 2x3 - 3x2 + 3x + 3

C) x4 + 2x3 - 3x2 + 3x + 2 + (3/x - 5)

D) x4 + 2x3 - 3x2 + 3x - 2 + (5/x - 5)

5) (x3 + (10/3)x2 + 3x + (2/3)/x + (1/3))

A) x2 + 3x + 4

B) x2 - (13/3)x + (38/x + 1)

C) x2 - (13/3)x + (14/9) - (16/27)

D) x2 + 3x + 2

6) (x5 - 1/x - 1)

A) x4 + x3 + x2 + x + 1 + (1/x - 1)

B) x5 + x4 + x3 + x2 + x + 1

C) x4 + x3 + x2 + x + 1

D) x5 + x4 + x3 + x2 + x + 1 + (1/x - 1)

7) (-6x3 + 2x2 + 5x - 10) ÷ (x - 2)

A) -6x2 - 10x - 15 + (-25/x - 2)

B) -6x2 - 10x - 5 + (-10/x - 2)

C) -6x2 - 10x - 25 + (-40/x - 2)

D) -6x2 - 10x - 15 + (-40/x - 2)

8) (x4 + 81) ÷ (x - 3)

A) x3 + 3x2 + 9x + 27 + (81/x - 3)

B) x3 - 3x2 + 9x - 27 + (162/x - 3)

C) x3 + 3x2 + 9x + 27

D) x3 + 3x2 + 9x + 27 + (162/x - 3)

9) (2x3 + x2 - 3x + 2) ÷ (x + 3)

A) 2x2 - 5x + 12 + (- 34/x + 3)

B) 2x2 - 5x - 12 + (- 34/x + 3)

C) 2x2 - 5x - 12

D) 2x2 - 5x + 12

10) (3x4 - 2x3 - 10x2 + 15) ÷ (x - 2)

A) 3x3 + 4x2 - 2x - 4 + (-11/x - 2)

B) 3x3 + 4x2 - 2x - 4 + (7/x - 2)

C) 3x3 + 4x2 - x - 3 + (1/x - 2)

D) 3x3 + 4x2 - 2x + 4 + (-8/x - 2)

Use the remainder theorem to find P(k).

11) k = -3; P(x) = 2x3- 4x2 - 4x + 9

A) -69

B) -93

C) -39

D) -9

12) k = 3; P(x) = 6x4+ 9x3 + 4x2 - 4x + 51

A) 1,440

B) 168

C) 804

D) 2,334

13) k = -3; P(x) = x2 + 2x + 2

A) 5

B) -17

C) 1

D) -13

14) k = -3; P(x) = -x3 + 3x2 + 2

A) -59

B) 56

C) 3

D) -56

15) k = 2; P(x) = x3 - 4x2 - 4x - 2

A) -18

B) -34

C) -32

D) -14

16) k = 1; P(x) = -4x5 + 2x3 - 2x2 - 2

A) -2

B) 2

C) -6

D) -5

17) k = -3; P(x) = x6 - 3x5 + 3x4 - 3x3 - 2x2 - 5x + 6

A) 1,786

B) 1,785

C) 135

D) -1,785

18) k = - (1/2); P(x) = 4x3 - 12x2 - 9x

A) 4

B) 2

C) 0

D) 1

19) k = 4 + i; P(x) = x3 + 11

A) 52 + 48i

B) 63 + 47i

C) 63 + 48i

D) 52 + 47i

20) k = -5 - 2i; P(x) = x2 + 3x + 5

A) 25

B) 11 + 4i

C) 11 + 14i

D) 6 + 4i

Use synthetic division to decide whether the given number is a solution of the given equation.

21) 4x3 + 2x2 + x + 3; x = -1

A) Yes

B) No

22) 8x3 + x2 - 2x + 7; x = -1

A) Yes

B) No

23) x4 + 7x2 - 144; x = -3

A) Yes

B) No

24) -x4 - 5x2 - x - 1; x = -2

A) Yes

B) No

25) -3x4 + 44x3 - 2x + 1; x = - (1/3)

A) Yes

B) No

26) -3x4 - 3x2 - 4; x = - (2/3)

A) Yes

B) No

27) x2 + 2x + 10; x = -1 - 3i

A) Yes

B) No

28) x2 - 6x + 25; x = -3 - 4i

A) Yes

B) No

29) x3 + 4x2 + 49x + 196; x = 7i

A) Yes

B) No

30) x3 + 5x2 - 12x + 14; x = 2 + i

A) Yes

B) No

## Solution 5 (1 Ratings )

Solved
Algebra 2 Months Ago 22 Views
This Question has Been Answered!